Seedling response to water stress in valley oak ( Quercus lobata ) is shaped by different gene networks across populations - Alayna Mead; Juan Peñaloza Ramirez; Megan K. Bartlett; Jessica W. Wright; Lawren Sack; Victoria L. Sork (Molecular Ecology, 2019)
Drought is a major stress for plants, creating a strong selection pressure for traits that enable plant growth and survival in dry environments. Many drought responses are conserved species‐wide responses, while others vary among populations distributed across heterogeneous environments. We tested how six populations of the widely distributed California valley oak ( Quercus lobata ) sampled from contrasting climates would differ in their response to soil drying relative to well‐watered controls in a common environment by measuring ecophysiological traits in 93 individuals and gene expression (RNA‐seq) in 42 individuals. Populations did not differ in their adjustment of turgor loss point during soil drying, suggesting a generalized species‐wide response. Differential expression analysis identified 689 genes with a common response to treatment across populations and 470 genes with population‐specific responses. Weighted gene co‐expression network analysis (WGCNA) identified groups of genes with similar expression patterns that may be regulated together (gene modules). Several gene modules responded differently to water stress among populations, suggesting regional differences in gene network regulation. Populations from sites with a high mean annual temperature responded to the imposed water stress with significantly greater changes in gene module expression, indicating that these populations may be locally adapted to respond to drought. We propose that this variation among valley oak populations provides a mechanism for differential tolerance to the increasingly frequent and severe droughts in California.